Venous Thromboembolism in Pediatric Vascular Anomalies - Nakano, Taizo A.; Zeinati, Chadi (Frontiers in Pediatrics, 2017)
The presence of a vascular anomaly suggests that capillaries, veins, arteries, and/or lymphatic vessels have demonstrated abnormal development and growth. Often dilated and misshaped, these vessels augment normal flow of blood and lymphatic fluids that increases the overall risk to develop intralesional thrombosis. Abnormal endothelial and lymphoendothelial cells activate hemostasis and hyperfibrinolytic pathways through poorly understood mechanisms, which contribute to the development of localized intravascular coagulopathy. Vascular malformations, tumors and complex combined syndromes demonstrate varying degrees of prothrombotic activity and consumptive coagulopathy depending on the vessels involved and the pattern and extent of abnormal growth. The clinical impact of venous thromboembolism in pediatric vascular anomalies varies from painful syndromes that disrupt quality of life to life threatening embolic disease. There remains little literature on the study, evaluation and treatment of thrombosis in pediatric vascular anomalies. However, there have been great advances in our ability to image complex lesions, to surgically and interventionally augment disease, and to provide enhanced supportive care including patient education, compression therapy and strategic use of anticoagulation.